Parabolic reflector fed by Cylindrical Dielectric Resonator Antenna with high gain - Ali, S.M. (IEEE Computer Society, 2014)
A single element circular slot aperture coupled Cylindrical Dielectric Resonator Antenna (CDRA) with a parabolic reflector is simulated and presented. The measured bandwidth of the single element CDRA is about 1.8 (5.32 - 5.52) while the simulated bandwidth is 1.11 (5.32 - 5.44 GHz). A comprehensive parametric study has been conducted to realize the effects of reflector parameters to increase the directivity of the designed antenna. The simulation of the antenna with parabolic reflector shows that it can enhance the gain about 240 as compared to the single element CDRA without reflector. The experimental results show that the antenna covers 5 GHz band, which satisfies the basic requirement of the WLAN application IEEE 802.11a. Â© 2014 IEEE.